Justice as the pillar of Islamic society in the Islamic civilisation as saviour of mankind: how to reconstruct it? - Mhd Sarif, Suhaimi; Yahya, Rohaziah (Sejahtera Consumerism Kulliyyah of Economics and Management Sciences IIUM, 2025)
Justice (al-‘adl) is the indispensable foundation upon which Islamic civilisation was historically constructed and magnificently sustained. Without justice, no society can endure in stability, while with justice, a civilisation radiates as a luminous beacon of mercy, balance, and divine guidance for humanity. This chapter meticulously examines the Qur’anic injunctions on justice, particularly Surah al-Nisā’ (4:58, 4:135), with interpretative insights from Ibn Kathīr and Hamka’s Tafsīr al-Azhar. The arguments emphasise that justice must be consistently realised at multiple levels: justice with Allah, justice with the self, justice with others, and justice with creation. Historically, Islamic civilisation emerged as a dynamic saviour of mankind through just governance, equitable trade, inclusivity, and knowledge cultivation, most vividly exemplified during the caliphate of ʿUmar ibn al-Khaṭṭāb (RA), the dazzling pluralism of Andalusia, and the institutionalisation of waqf. Justice is not merely a legal imperative but a continuous form of worship (ʿibādah), wherein fairness in leadership, education, economy, and social relations constitutes obedience to Allah. The chapter further explores contemporary pathways for reconstructing Islamic civilisation by embedding justice in governance, education, economy, society, and environmental stewardship. Conclusively, justice stands as the ultimate guarantor of peace, harmony, and sustainability, positioning Islamic civilization to once again serve humanity with compassion, wisdom, and divine balance.